Ijtihad terhadap Praktik Shalat Berjamaah dengan Imam Hologram dalam Perspektif Hukum Islam Kontemporer - Muhammad Ihsan; Dwi Shafanuha; Salsabila Fatia Azarah (LPPM Universitas Potensi Utama, 2026)
The development of hologram technology has created new discussions in religious practices, one of which is the use of hologram imams during congregational prayers. This phenomenon raises serious fiqh issues because it touches on the fundamental aspects of mahdhah worship, which is tauqīfiyyah. The purpose of this study is to examine the practice of congregational prayer with a hologram imam from the perspective of modern Islamic law through the method of ijtihad fiqh. The method used in this study is normative legal research with a conceptual and comparative approach, as well as an analysis of relevant primary and secondary legal sources. The research findings indicate that the practice of congregational prayer with a hologram imam cannot be equated with conventional imams, due to the lack of the imam's physical presence and the severance of the principal connection (ittiṣāl) between the imam and the congregation. Furthermore, the use of hologram technology in this context is considered to have exceeded the function of wasīlah and has the potential to change the essence of worship itself. When viewed from the perspective of maqāṣid al-sharī‘ah, this practice tends to produce greater mafsadat than maṣlaḥat. Therefore, this study concludes that the implementation of congregational prayers with a hologram imam cannot be considered valid according to current Islamic law.